Coarse dust particle transport model around Malmberget mining area - Huang, Yi (Luleå tekniska universitet, Geoteknologi, 2012)
The dust generated from mining activities in the mining area is an important environmental issue for modern mining industries with many environmental problems involved. Number of researcher worked on small dust particle transport, but few work related to the coarser dust particles with 10 to 100 micro meters diameters had been made despite the fact that coarser dust transport have significant influence on the human lives (e.g. dust deposit on the residential area nearby, and mining facilities which may bring commercial and safety problem to the people living close by and the mine operators). More complaints from the residents and the workers deserve such research work.The research on dust transport is aiming to track how dust transport and deposit around the mining area and its interrelationship with local climate and topographic conditions. The modeling work is based on some fluid sediment transport dynamic models, with 1D, 2D and 3D when the research steps go further on. The models illustrate the transport progress and the amount transported by the wind. A case study from Malmberget mine in northern Sweden has been made in 2010.The dust characteristic information was obtained from laboratory work in LTU, and local climate information was supplied by the SMHI (Swedish Meteorological and Hydrological Institute). Two transport models were developed and applied here: One is the computational model based upon the classical Bagnold’s (1941) equation; and the other one is the simulation model based upon the sedimentation engineering work from Al-Ansari (1976). The computational model calculates dust retention time for estimating the amount of dust transport in certain time period with provided wind and dust characteristic information. The simulation model used simple sediment transport model to simulate the dust grain movement in air flow, and conclude the transport amount of dust. Both models were enhanced by Matlab GUI to simplify the calculation procedure. The comparison of the results from the two models gave the ...